COMMUNICATION STYLES AND MASCULINE IDENTITY IN GIOVANNI’S ROOM AND THE GREAT GATSBY (Ustozlar uchun, 2026)
This article examines the relationship between communication styles and masculine identity construction in Giovanni’s Room by James Baldwin and The Great Gatsby by F. Scott Fitzgerald. Though separated by historical context and thematic focus, both novels explore masculinity as a fragile and performative construct shaped through speech, silence, confession, and narrative control. Drawing on gender theory, discourse analysis, and queer theory, this study argues that communication functions not merely as expression but as a mechanism of power and identity formation. While Fitzgerald presents masculinity through performative dialogue and narrative mediation within a heteronormative and class-conscious society, Baldwin foregrounds confession, repression, and emotional articulation within a context of sexual identity crisis. Through comparative textual analysis, the article demonstrates that communication styles in both works reveal masculinity as unstable, socially regulated, and deeply dependent on recognition and discourse.